Free speech in classical antiquity - Sluiter, I. (Ineke); Rosen, Ralph Mark (Mnemosyne, bibliotheca classica Batava. Supplementum, 2004)
This book contains a collection of essays on the notion of "Free Speech" in classical antiquity. The essays examine such concepts as "freedom of speech," "self-expression," and "censorship," in ancient Greek and Roman culture from historical, philosophical, and literary perspectives. Among the many questions addressed are: what was the precise lexicographical valence of the ancient terms we routinely translate as \'Freedom of Speech,\' e.g., Parrhesia in Greece, Licentia in Rome? What relationship do such terms have with concepts such as isêgoria , dêmokratia and eleutheria ; or libertas , res publica and imperium ? What does ancient theorizing about free speech tell us about contemporary relationships between power and speech? What are the philosophical foundations and ideological underpinnings of free speech in specific historical contexts?